2021
DOI: 10.1136/bmjgast-2021-000670
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with IBD during the COVID-19 pandemic in the Netherlands

Abstract: ObjectiveCOVID-19 has put a strain on regular healthcare worldwide. For inflammatory bowel disease (IBD), gastrointestinal surgeries were postponed and changes in treatment and diagnostic procedures were made. As abrupt changes in treatment regimens may result in an increased morbidity and consequent well-being of patients with IBD, the aim of this study was to determine the effect of the COVID-19 pandemic on health-related quality of life (HRQoL) in patients with IBD.DesignAll patients with IBD who completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…The results of our study support data from the literature [ 26 , 27 ]. A recent study evaluating the effects of social isolation and emotional stress on patients with IBD during the COVID-19 pandemic showed that isolation at home was associated with an increase in the frequency of stress episodes (50.8%) and gastrointestinal, predominantly functional symptoms, while the decrease in the frequency of stress episodes (11.1%) was associated with a decrease in gastrointestinal symptoms [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study support data from the literature [ 26 , 27 ]. A recent study evaluating the effects of social isolation and emotional stress on patients with IBD during the COVID-19 pandemic showed that isolation at home was associated with an increase in the frequency of stress episodes (50.8%) and gastrointestinal, predominantly functional symptoms, while the decrease in the frequency of stress episodes (11.1%) was associated with a decrease in gastrointestinal symptoms [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similar results have been noted among IBD patients. Although some studies indicate lower quality of life as an effect of the pandemic, other investigators support that despite recent barriers in IBD patients' healthcare, such as delays in procedures, appointments, and drug inaccessibility, the quality of life has not changed significantly [21][22][23][24]. For example, in the Netherlands, investigators reported worsening in quality of life and gastrointestinal symptomatology, but a tertiary care center in Saudi Arabia did not reveal worsening in IBD patients' quality of life [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies indicate lower quality of life as an effect of the pandemic, other investigators support that despite recent barriers in IBD patients' healthcare, such as delays in procedures, appointments, and drug inaccessibility, the quality of life has not changed significantly [21][22][23][24]. For example, in the Netherlands, investigators reported worsening in quality of life and gastrointestinal symptomatology, but a tertiary care center in Saudi Arabia did not reveal worsening in IBD patients' quality of life [23,24]. The insignificant changes in symptoms observed by some studies could also be attributed to the fact that IBD patients may have been more socially isolated even prior to the pandemic due to the overwhelming symptomatology they usually suffer from.…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out by means of questionnaires have shown that the quality of life of IBD patients, particularly in older people, females and patients who underwent surgery, was significantly reduced during pandemic. In many cases limitations were due to mental health and emotional health problems ( 47 ).…”
Section: Clinical Course and Severity Of Covid-19 In Patients With In...mentioning
confidence: 99%